2013
DOI: 10.1016/j.jhazmat.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Environmental arsenic contamination and its health effects in a historic gold mining area of the Mangalur greenstone belt of Northeastern Karnataka, India

Abstract: This report summarizes recent findings of environmental arsenic (As) contamination and the consequent health effects in a community located near historic gold mining activities in the Mangalur greenstone belt of Karnataka, India. Arsenic contents in water, hair, nail, soil and food were measured by FI-HG-AAS. Elemental analyses of soils were determined by ICP-MS (inductively coupled plasma-mass spectrometry). Of 59 tube-well water samples, 79% had As above 10 μg L−1 (maximum 303 μg L−1). Of 12 topsoil samples,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 30 publications
0
39
1
3
Order By: Relevance
“…3b) which is a common characteristic of a site where contaminant transport is driven by local climate and hydrology (Jung, 2001, Lim et al, 2008, Navarro et al, 2008, Romero et al, 2010, Hajalilou et al, 2011, Chakraborti et al, 2013, Antunes and Albuquerque, 2013and Silva et al, 2013. Metal distribution is dependent upon the form of the contaminant.…”
Section: Standard Guideline Valuesmentioning
confidence: 99%
“…3b) which is a common characteristic of a site where contaminant transport is driven by local climate and hydrology (Jung, 2001, Lim et al, 2008, Navarro et al, 2008, Romero et al, 2010, Hajalilou et al, 2011, Chakraborti et al, 2013, Antunes and Albuquerque, 2013and Silva et al, 2013. Metal distribution is dependent upon the form of the contaminant.…”
Section: Standard Guideline Valuesmentioning
confidence: 99%
“…This area also has several historic gold mines with some presently active and many abandoned. 7,9 In the current study 100 inhabitants of the village participated in the questionnaire survey of which majority were in the age group of 25-38 years. It was observed that 81% of the participants were aware of the gold mining in Hutti.…”
Section: Discussionmentioning
confidence: 99%
“…8 Finally, infants and children are sometimes directly exposed to the mining processes themselves, since mothers often have their children at the mine site and processing areas while they are working and sometime young children even participate in mining as workers. 9 Hence a questionnaire based survey was conducted amongst the local population of the Hatti village. The primary objective of this survey was to assess community risk knowledge and perception of potential Mercury and Arsenic toxicity and/or exposure from artisanal gold mining in the Hatti village locality.…”
Section: Introductionmentioning
confidence: 99%
“…Chakraborti et al [34] assessed the environmental (groundwater, soil and vegetables) and human biomarker As levels to determine health effects in a community level where arsenicosis cases were previously reported. Rahman et al [35] determined the quantity of As and other elements ingested through drinking water and vegetables by adult members in Noakhali district, Bangladesh for exposure assessments.…”
mentioning
confidence: 99%